MDSC subtypes and CD39 expression on CD8+ T cells predict the efficacy of anti‐PD‐1 immunotherapy in patients with advanced NSCLC. Issue 11 (9th July 2020) - Koh, Jiae; Kim, Youjin; Lee, Kyoung Young; Hur, Joon Young; Kim, Mi Soon; Kim, Boram; Cho, Hee Jin; Lee, Yeong Chan; Bae, Yeon Hee; Ku, Bo Mi; Sun, Jong‐Mu; Lee, Se‐Hoon; et al.
Abstract: The major suppressive immune cells in tumor sites are myeloid derived suppressor cells (MDSCs), tumor‐associated macrophages (TAMs), and Treg cells, and the major roles of these suppressive immune cells include hindering T‐cell activities and supporting tumor progression and survival. In this study, we analyzed the pattern of circulating MDSC subtypes in patients with non‐small cell lung cancer (NSCLC) whether those suppressive immune cells hinder T‐cell activities leading to poor clinical outcomes. First, we verified PMN‐MDSCs, monocytic‐MDSCs (M‐MDSCs), and Treg cells increased according to the stages of NSCLC, and MDSCs effectively suppressed T‐cell activities and induced T‐cell exhaustion. The analysis of NSCLC patients treated with anti‐PD‐1 immunotherapy demonstrated that low PMN‐MDSCs, M‐MDSCs, and CD39 + CD8 + T cells as an individual and all together were associated with longer progression free survival and overall survival, suggesting PMN‐MDSCs, M‐MDSCs, and CD39 + CD8 + T cells frequencies in peripheral blood might be useful as potential predictive and prognostic biomarkers. Abstract : Pre‐existing PMN‐MDSCs, M‐MDSCs, and CD39 + CD8 + T cells can be used as predictive biomarkers in anti‐PD‐1 immunotherapy targeting NSCLC. Together with MDSCs, IL‐10 possibly released by suppressive immune cells also leads poor clinical outcomes. Therefore, combinatorial strategies targeting MDSCs or IL‐10 should be investigated to improve outcomes of immune checkpoint inhibitors.